1996
DOI: 10.1074/jbc.271.17.9934
|View full text |Cite
|
Sign up to set email alerts
|

Selective Uptake of Cytosolic, Peroxisomal, and Plasma Membrane Proteins into the Yeast Lysosome for Degradation

Abstract: When glucose-starved cells are replenished with glucose, the key gluconeogenic enzyme, fructose-1,6-bisphosphatase (FBPase), is selectively targeted from the cytosol to the yeast lysosome (vacuole) for degradation. The glucose-induced targeting of FBPase to the vacuole for degradation occurs in cells grown under a variety of metabolic conditions. Immunoelectron microscopic studies demonstrate that the uptake of FBPase by the vacuole is mediated in part by an autophagic process. FBPase can be found on the vacuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(107 citation statements)
references
References 43 publications
6
101
0
Order By: Relevance
“…Although the site of FBPase degradation has been a matter of debate (21,22), a PEP4-dependent degradation of FBPase has been shown by our laboratory and confirmed by an independent research group (23). Using immunofluorescence and immunoelectron microscopy, we showed that FBPase is localized to the vacuole in the pep4 strain (18,19). In addition, FBPase trafficking to the vacuole has been reconstituted using a semi-intact pep4 strain (20).…”
mentioning
confidence: 88%
“…Although the site of FBPase degradation has been a matter of debate (21,22), a PEP4-dependent degradation of FBPase has been shown by our laboratory and confirmed by an independent research group (23). Using immunofluorescence and immunoelectron microscopy, we showed that FBPase is localized to the vacuole in the pep4 strain (18,19). In addition, FBPase trafficking to the vacuole has been reconstituted using a semi-intact pep4 strain (20).…”
mentioning
confidence: 88%
“…Presumably, glucose stimulates a receptor protein in the membrane of the vacuole. Whether the mechanism of vacuolar uptake involves microautophagy or a chaperonin-mediated direct translocation of fructose 1,6-diphosphatase into the vacuole, or a combination of both, is not entirely clear (Chiang et al, 1996). An alternative view is that fructose 1,6-phosphatase is not targeted to the vacuole but, instead, is degraded via the ubiquitinproteasome pathway (Schork et al, 1995).…”
Section: Selective Targeting Of Cytosolic Proteins To Lysosomesmentioning
confidence: 99%
“…However, when glucose replaces methanol, peroxisomes are taken up directly by the vacuoles by a process resembling microautophagy, which is sensitive to inhibition by cycloheximide (Tuttle & Dunn, 1995). Similarly, when glucose-starved S. cerevisiae cells are replenished with glucose, peroxisomes are degraded by microautophagy (Chiang et al, 1996).…”
Section: Specificity Of Macroautophagymentioning
confidence: 99%
“…For these experiments, aliquots of cells (1 A 600 ) were used for each time point. Rabbit anti-FBPase antibodies were produced as described previously (30,31). The ⌬pep4⌬prb1⌬prc1 strain (45) was obtained from Dr. A. Kornberg (Stanford University).…”
Section: Methodsmentioning
confidence: 99%